The Role of Consumer Behavior and Personal Selling in Determining Purchasing Decisions at Panji Teknik Stores - Dina Ari Putu Dina Ari Susanti; I Gusti Made Oka Astana (ARTHA SATYA DHARMA, 2023)
This study aims to determine whether consumer behavior and personal selling influence purchasing decisions at Toko Panji Teknik. This research approach uses a quantitative method which collects data by using a questionnaire and measuring a Likert scale of 1-5 with a total of 75 respondents. The data analysis technique used is multiple linear regression with the SPSS (Statistical Package for the Social Sciences) version 2.5 method. The results obtained from this study are that Rational Motives have a positive and insignificant effect on purchasing decisions, the results for Emotional Motives and Personal Selling variables have a positive and significant effect on purchasing decisions at Panji Teknik Stores.